Calcium Signaling in T Cells Is Induced by Binding to Nickel-Chelating Lipids in Supported Lipid Bilayers - Dam, Tommy; Junghans, Victoria; Humphrey, Jane; Chouliara, Manto; Jönsson, Peter (Frontiers in Physiology, 2021)
Supported lipid bilayers (SLBs) are one of the most common cell-membrane model systems to study cell-cell interactions. Nickel-chelating lipids are frequently used to functionalize the SLB with polyhistidine-tagged ligands. We here show that these lipids by themselves can induce calcium signaling in T cells, also when having protein ligands on the SLB. This is important both to avoid “false” signaling events in cell studies with SLBs, but also to better understand the molecular mechanisms involved in T-cell signaling. Jurkat T cells transfected with the non-signaling molecule rat CD48 were found to bind to ligand-free SLBs containing ≥2 wt% nickel-chelating lipids upon which calcium signaling was induced. This signaling fraction steadily increased from 24% to 60% when increasing the amount of nickel-chelating lipids from 2 wt% to 10 wt%. Both the signaling fraction and signaling time did not change significantly compared to ligand-free SLBs when adding the CD48-ligand rat CD2 to the SLB. Blocking the SLB with bovine serum albumin reduced the signaling fraction to 11%, while preserving CD2 binding and the exclusion of the phosphatase CD45 from the cell-SLB contacts. Thus, CD45 exclusion alone was not sufficient to result in calcium signaling. In addition, more cells signaled on ligand-free SLBs with copper-chelating lipids instead of nickel-chelating lipids and the signaling was found to be predominantly via T-cell receptor (TCR) triggering. Hence, it is possible that the nickel-chelating lipids act as ligands to the cell’s TCRs, an interaction that needs to be blocked to avoid unwanted cell activation.